Competency‐based Project to Review Community/Public Health Curricula. Issue 4 (8th November 2013) - Schoneman, Doris; Simandl, Gladys; Hansen, Judith M.; Garrett, Sharon
Abstract Changes in the delivery of community/public health (C/PH) nursing have challenged nursing educators to seek innovative ways to ensure that their educational programs produce competent entry‐level practitioners. This article describes how public health professionals and faculty from eight regional colleges and universities in Southeastern Wisconsin came together to better understand both what C/PH nursing content was being taught in the region, and the extent to which that content was aligned with the Public Health Nurse Competencies defined by the Quad Council in 2004. Based on self‐reporting by nursing school faculty as well as a separate mapping of course objectives into the competency areas, the project found that the curricula of the participating colleges and universities adequately addressed most of the competencies in the Quad Council domains one through six. Competencies in domains seven (financial planning/management skills) and eight (leadership/systems thinking skills) were not, however, adequately addressed and plans were subsequently developed to fill those gaps. In addition to helping each institution identify strengths and gaps in its own curriculum, the project provided an unprecedented opportunity for both public health professionals and academics to build relationships, share best practices, and exchange resources.